Immiscible fluid flow through nanotubes - Marañón Di Leo, Julio (2003)
We have analyzed the properties that characterize the water/oil interface when flow occurs through a prismatic flexible surface of van der Waals particles at 300 K. Thermodynamics and dynamics properties of the flow as density profiles, interface width and diffusion coefficients were calculated. We have observed a complex mechanism, the back-and-forth movement of the interface when advancing through a nanotube.